Outbound Method to Improve Group B Children's Cooperation Ability - Fransiska Ni Kadek Sonia Puranta Putri; Ni Luh Ayu Tirtayani (Universitas Pendidikan Ganesha, 2023)
The lack of application of creative learning methods hinders children's focus in completing assignments. This research aims to determine the significant effect of using the outbound method to improve group B children's cooperative abilities, such as interpreting instructions and directing when mistakes occur. This type of research is a quasi-experiment with a non-equivalent control group design. The population in this study was 38 children. Research samples were taken using random sampling techniques. The selected models were Group B1, with 20 children as the experimental group, and Group B2, with 18 children as the control group. The data collection method used is a non-test method, namely observation with an analysis method using inferential statistics. The results of this study showed that the average post-test score for the experimental group was 95.17, while for the control group, it was 63.28. The results of data analysis obtained a count of 18.58. The data analysis shows that using the outbound method affects the cooperative abilities of group B children. It is concluded that the outbound process can improve the collective skills of group B children.